Selection of Outstanding Lecturers Using the AHP and Promethee Methods: Selection of Outstanding Lecturers Using the AHP and Promethee Methods - Rizki Insani Maulana; Septi Andryana; Deny Hidayatullah (Institute of Computer Science (IOCS), 2020)
National University is the oldest private university in Jakarta and second in Indonesia, the University was founded on October 15, 1949. At this University there are several bureaus to take care of various university needs, one of which is the human resources bureau. Human resources bureau is a bureau that regulates various human resources available at the National University, including lecturers and other employees. In this study, every lecturer who teaches at the National University is carried out assessment and to see which lecturer has the most achievement compared to the others, making it easier for the campus, especially the human resource bureau to conduct evaluations that are useful for improving the quality of teaching provided by lecturers who teaches on this campus. Then it can also help the campus to give rewards to outstanding lecturers so that they can further improve their abilities. In determining this outstanding lecturer, several objective criteria are needed. Research in this application uses the AHP method and the PROMETHEE method. Meanwhile, to operate this application, this application will be based on the website.